UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK MELALUI KEGIATAN BERHITUNG MENGGUNAKAN STRATEGI JOYFUL LEARNING DI KELAS B TK SALSABILA DESA SIHEPENG TOLU - ainun mardiah; sri wahyuni; rosmaimunah siregar; jumaita nopriani lubis (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The cognitive ability of children in grade B of Salsabila Kindergarten, Sihepeng Tolu Village, still has to be improved, this is due to the lack of teacher creativity in the use of learning andnumeracy media. The purpose of this classroom action research is to improve children's cognitive abilities through numeracy activities using joyful learning strategies. Classroom action research was carried out in grade B of Salsabila Kindergarten in Sihepeng Tolu Village which amounted to 15 children using the method of Planning, Action, Observation, and Reflection. Data collection techniques include interviews, observations, and documentation. This study was conducted in three cycles with 7 meetings. Based on the results of observations, cycle 1 has not reached the success target. Pno cycle 2 is still 73.3 %. Incycle 3 the seventh meeting was already successful at the stage of Developing very well. Thus, it was concluded that classroom action research through numeracy activities using joyful learning strategies can improve children's cognitive abilities.